Men's perceptions of the impact of the physical consequences of radical prostatectomy on their quality of life: a qualitative systematic review protocol. (December 2015) - Morgan, Laura; Carrier, Judith; Edwards, Deborah
Abstract : Review question/objective : The objective of this review is to explore men's perceptions of the impact of the physical consequences of radical prostatectomy on their quality of life Background : Prostate cancer is the most common male cancer and second most common cause of cancer death in men in the Western world.1 The quality of life of men with prostate cancer can be negatively affected by the various treatments available to them.2 Radical prostatectomy is the predominant primary treatment approach for prostate cancer in a number of countries including Australia and North America, 3, 4 and involves the complete removal of the prostate, seminal vesicles and surrounding tissues.5 Postoperative complications commonly occur and current literature reports issues concerning the bladder, bowel and sexual dysfunction.6 Each of these can be categorized as a physical consequence of the surgery and for radical prostatectomy such complications are urinary7, 8 and fecal incontinence9 as well as sexual dysfunction.7 These physical consequences of surgery are intrinsically connected to psychosocial implications for the patient and are associated with significantly reduced quality of life.5, 10 Urinary incontinence is a problem for at least 50% of men who undergo radical prostatectomy and this can have a negative effect on their postoperative quality of life.7‐11 Men can experience negative feelings about dealing with indwelling catheters and urinary incontinence at home, and report anxiety, fear and embarrassment.11 as well as a loss of a sense of control, depression and decreased social interactions.8 Fecal incontinence is also reported to have a significant impact on men's self‐confidence, personal image and social life.5, 9 Sexual dysfunction following radical prostatectomy encompasses several physical issues including erectile dysfunction and impotence, 12, 13 which is one of the most common concerns of men post radical prostatectomy.14, 15 A number of psychological and relationship implications have been highlighted, 16 and many men do not know where to turn to for help.15 A less common physical issue following radical prostatectomy is penile length shortening.8 Yoko et al.8 suggest that, from the viewpoint of society and its preoccupation with penile size, physical reduction in penile length size following radical prostatectomy can negatively affect psychological well‐being. An important clinical implication for understanding men's perceptions of the physical and psychosocial consequences of radical prostatectomy is that healthcare professionals working with these men can assist them in considering and discussing issues such as masculinity, erectile dysfunction and incontinence pre‐ and post‐treatment, thereby increasing men's understanding and adaptation postoperatively.17, 18 A national survey of cancer patients conducted in the United Kingdom (UK) in 1999/2000 identified that patients with prostate cancer often had a worse experience of supportive care than those diagnosed with and treated for other cancers.4 A second survey, conducted following the implementation of the NHS Cancer Plan, 19 a program outlining the UK government's intentions to reform cancer care, was consistent with the results of the 1999/2000 survey and identified only the smallest improvement in the provision of care for patients with prostate cancer.20 A more recent survey21 identified improvement in the patient's perception of their experience of prostate cancer care. Even so, the care of people suffering from prostate cancer fell behind several other cancer groups (breast, lung and colorectal) on multiple elements of the survey, including definitive explanations of the potential side effects of treatment thereby highlighting scope for improvement in care provision. The National Institute for Health and Care Excellence guidelines for prostate cancer22 emphasizes the pivotal role of communication between healthcare professionals and men with prostate cancer. One of their key priorities is the healthcare professionals' role in providing evidence‐based advice regarding the potential side effects of prostate cancer treatment and subsequent support that takes into account quality of life implications for these men. Treatment such as radical prostatectomy that has negative physical and psychosocial consequences that potentially impact on men's quality of life means it is increasingly becoming an important topic. Willener and Hantikainen23 suggest that improving quality of life should be the ultimate aim of any healthcare treatment or intervention, and the patient's experience of the treatment is paramount. In order to provide high quality care, healthcare professionals need to improve understanding of the physical and psychosocial implications of radical prostatectomy from the men's perspective.11 An improved understanding of the men's perspective of these physical consequences could potentially enhance the value and impact of support provided. The underpinning concept in this proposed review is to explore the repercussions on lifestyle and associated psychosocial impact that the outlined physical consequences have on men following radical prostatectomy. By identifying and exploring issues that affect men's quality of life, opportunities can be created to talk about problems, discuss issues and ultimately improve men's postoperative experiences. Nurses provide a vital role in ensuring that men are adequately prepared for radical prostatectomy and the potential implications on their postoperative quality of life.15 Without an in depth knowledge and understanding of men's experiences post radical prostatectomy, there is a risk that health professionals may be unable to provide the comprehensive support and information that is vital to men postoperatively. Numerous qualitative studies have been published exploring men's post radical prostatectomy surgery experiences14, 15, 18, 24‐28 and also those from the point of view of their spouses.6, 29, 30 Previous qualitative reviews in this area are limited and a search revealed only one narrative review of men's experiences of urinary incontinence after prostatectomy.11 The majority of systematic reviews conducted were quantitative, and they investigated health related quality of life following radical prostatectomy5, 10 and the effectiveness of psychoeducational interventions on urinary and fecal incontinence and erectile dysfunction in men over 50 years and over after prostatectomy for prostate cancer in comparison to usual care.31 A systematic review exploring the findings of studies that specifically discuss the impact of the physical consequences of radical prostatectomy on their quality of life is essential to assist health care professionals in focusing on this area in future practice. To date no such systematic review has been conducted.